The Effect of Dysmenorrhea Gymnastics on the Pain Scale of Dysmenorrhea in Young Women - Ekapuspitasari, Dita Yanuar; Sari, Yeni Kartika; Widigdo, Trio (Dewan Pimpinan Daerah Persatuan Perawat Nasional Indonesia Kota Blitar, 2023)
Teenager women experience growth and development, one of which is characterized by the occurrence of haid. Dysmenorrhoea is often found at the beginning of menstruation young women experience menstrual pain. Exercise in this case gymnastics dysmenorrhea is shown to increase b-endorphin 4 to 5 times in the blood. Data obtained from the youth poly of UPT Puskesmas Kec. Sananwetan in September 2020 showed that 2 out of 5 PSBR teenagers who came to the UPT Puskesmas Kec. Sananwetan experienced complaints of dysmenorrhea every month. Research aims to determine the effect of giving Dysmenorrhea gymnastics on young women in PSBR Blitar City. This study included a quasi-experimental study with a population of 35 young women and samplingusing Purposive Sampling. Based on the results of a study conducted using a dependent T-test statistical test (dependent T-test), the time of dysmenorrhea pain before dysmenorrhea gymnastics in young women was 4 (16%) adolescents experiencing mild dysmenorrhea pain, 12 (48%) adolescents experiencing moderate pain, and 9 (36%) adolescents experiencing severe pain scale, dysmenorrhea pain scale after dysmenorrhea gymnastics in young women is 3 (12%) adolescents do not experience dysmenorrhea pain, 22 (88%) adolescents experience moderate pain. This study proves that dysmenorrheagymnastics has a significant influence on the scale of dysmenorrhea pain in adolescents in the Social Service of Youth Development (PSBR) of Blitar City.